ANALISIS IMPLEMENTASI PELAKSANAAN ANGGARAN BADAN LAYANAN UMUM DAERAH (BLUD) PADA RUMAH SAKIT UMUM DAERAH ANUTAPURA KOTA PALU (Studi Pada Rumah Sakit Umum Anutapura Kota Palu) - Sutrini, Sutrini (Katalogis, 2017)
Singer study aims to review analyze and describe the depth Operating Regarding the Implementation of the Budget Implementation Regional Public Service General Hospital Anutapura ON Palu. Both for the review to know and analyze the factors inhibiting the implementation of the Budget Implementation BLUDs IN RSU Anutapura Palu. The data analysis used descriptive analysis interprektif. Results Of Research Singer gives CONCLUSION: (1) the implementation of the Budget Implementation BLUDs, General Hospital Anutapura Palu Palu Mayor refers ON Regulation No. 61 Year 2007 Financial Management ON Regional Public Service As well as the author adopts Opinion C.Edwar George III (1980) can be Seen From the dimensions of communication, resources, disposition and Bureaucratic Structure rated has undertaken to support the Budget Implementation In managed Finance hearts Stylists BLUDs Transparent and accountable. (2) inhibiting factors hearts Implementation of the Budget Implementation BLUDs IN RSU Anutapura Palu is First ON Acceptance Namely PT Patra Telekomunikasi findings singer was supported by the responses AT respondents Where Not Orderly, the process is efficient, economical, transparent and bertaggung responsible As well as can be provide Value Added, According WITH A healthy business practices bedasarkan Regulation No. 23 of 2005. Both the surflus end of the year do not require a cash deposit of funds remaining All areas are however obliged to Report Under the Government Regulation.